Predictors of Parental Contentment with the Amount of Encouraging Digital Feedback from Teachers in Finnish Schools - Anne-Mari Kuusimäki; Lotta Uusitalo; Kirsi Tirri (MDPI AG, 2021)
The Finnish National curriculum obligates teachers to give parents encouraging feedback about their children's learning and development, the aim being to build a constructive relationship between homes and schools and to encourage close collaboration among all parties. Teachers in Finland nowadays use digital platforms that allow effective online communication. The frequency and quality of such communication vary a great deal. In particular, there seems to be a lack of clarity concerning the amount of encouraging feedback delivered in this way. The focus in this paper is on the extent to which Finnish parents (N = 1117) in both urban and rural areas are content with the amount of such feedback. We carried out a logistic regression analysis to predict parental contentment with the amount of encouraging messaging, with the pupil's grade level, parental attitudes to digital communication, as well as parental educational level and gender as independent variables. In sum, parents who were less highly educated, with a neutral-to-positive attitude to digital communication and with a child in lower secondary school were most likely to be content with the amount of communication. These results have both research and practical implications in terms of enhancing the understanding of how best to deliver encouraging digital feedback between homes and schools. Furthermore, it seems that teacher education should focus on communicative competence early on. The current study completes our three-part series of studies on digital home-school communication in Finland.